Pemberdayaan remaja putri melalui program holistik yoga modifikasi untuk peningkatan kesejahteraan biopsikososial: Empowering adolescent girls through a modified holistic yoga program to improve biopsychosocial well-being - Prafitri, Lia D.; Ersila, Wahyu; Chabibah, Nur; Nashiroh, Lailatun; Nada, Sabrina S. (IGKOJEI: Jurnal Pengabdian Masyarakat, 2026)
ABSTRACT  Adolescence is recognized as a critical developmental phase characterized by rapid biological, psychological, and social changes. Adolescent girls living in orphanages are identified as experiencing multiple vulnerabilities, including limited access to reproductive health services, low nutritional knowledge, elevated levels of stress and anxiety, and restricted social skills. These conditions are considered to require holistic and participatory empowerment interventions. The program was developed as a science- and technology-based empowerment model in which nutrition and reproductive health education, modified yoga practice, peer group strengthening through role-play, and life skills training were integrated. This Community Service Program was conducted over eight months at Aisyiyah Putri Orphanage in Pekajangan, Pekalongan Regency, and involved 20 adolescent girls aged 13–18 years. The intervention was implemented through Focus Group Discussions (FGDs), educational sessions, demonstrations, yoga practice delivered by a certified instructor, mentoring activities, and pre–post evaluations using a validated and reliable questionnaire (α = 0.72). Significant improvements in knowledge were observed, with mean scores increasing from 62.5 to 78.4. Reductions in stress levels (20.1 to 14.8) and anxiety (from 18.2 to 12.7), were also recorded, while psychosocial scores were found to improve from 65.7 to 75.2. These findings indicate that a participatory communication approach integrating health education, modified yoga, and peer group activities is effective in strengthening adolescents’ holistic capacities. The program is considered a relevant biopsychosocial empowerment model for orphanage settings and is regarded as having strong potential for sustainability through institutional support and digital-based monitoring systems.  Keywords: Adolescent girls; Biopsychosocial well-being; Health education; Modified yoga; Peer group   ABSTRAK  Masa remaja merupakan fase perkembangan kritis yang ditandai perubahan biologis, psikologis, dan sosial yang cepat. Remaja putri di panti asuhan menghadapi kerentanan ganda, meliputi keterbatasan akses kesehatan reproduksi, rendahnya pengetahuan gizi, masalah psikologis seperti stres dan kecemasan, serta keterbatasan keterampilan sosial. Kondisi tersebut menuntut intervensi pemberdayaan yang holistik dan partisipatif. Program dikembangkan sebagai model pemberdayaan berbasis IPTEKS yang mengintegrasikan edukasi gizi dan kesehatan reproduksi, praktik yoga modifikasi, penguatan peer group melalui role play, serta pelatihan life skills. Kegiatan Pengabdian kepada Masyarakat ini dilaksanakan selama delapan bulan di Panti Asuhan Putri Aisyiyah Pekajangan Kabupaten Pekalongan dengan melibatkan 20 remaja putri usia 13–18 tahun. Metode yang digunakan meliputi Focus Group Discussion (FGD), edukasi, demonstrasi, praktik yoga oleh instruktur bersertifikat, pendampingan, serta evaluasi pre–post menggunakan kuesioner yang telah teruji validitas dan reliabilitasnya (α = 0,72). Hasil evaluasi menunjukkan peningkatan signifikan pada aspek pengetahuan (mean pre-test 62,5 menjadi 78,4), penurunan tingkat stres (20,1 menjadi 14,8) dan kecemasan (18,2 menjadi 12,7), serta peningkatan aspek psikososial (65,7 menjadi 75,2). Temuan ini menunjukkan bahwa pendekatan komunikasi partisipatif melalui integrasi edukasi kesehatan, yoga modifikasi, dan peer group efektif meningkatkan kapasitas remaja putri secara holistik. Program terbukti relevan sebagai model komunikasi pemberdayaan remaja berbasis pendekatan biopsikososial di lingkungan panti asuhan. Program ini berpotensi dikembangkan secara berkelanjutan dengan memperkuat peran pengelola panti dan integrasi media digital untuk mendukung monitoring serta dampak jangka panjang. Kata kunci: Biopsikososial; Edukasi Kesehatan; Peer Group; Remaja Putri; Yoga Modifikasi